2002
DOI: 10.1007/s00428-001-0555-z
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidosis of the breast

Abstract: We report on three cases of amyloidosis of the breast, two of which coincided with breast cancer. Patient no. 1, a 60-year-old woman, presented with two mass lesions measuring 2 cm in diameter, one in each breast. Histologically, a tubulo-lobular carcinoma was found in the left breast accompanied by vascular, interstitial, and periductal amyloid deposits; the lesion in the right breast consisted of amyloid deposits only. Patient no. 2, an 86-year-old woman, presented with an ulcerated breast tumor measuring 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
4
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 30 publications
0
46
4
2
Order By: Relevance
“…Amyloid type was available in 18 of these 42 cases and was AL in 15 cases, AA in 2 cases and AH in 1 case. Interestingly, AL amyloidosis was kappa type in 60% of our cases and in 67% of the previously reported cases reviewed by Rocken et al 4 This is in contrast to AL amyloidosis in general, in which twothirds of cases are of lambda type. 17 Forty-seven percent of patients with breast amyloidosis seen at our medical center had systemic AL amyloidosis.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Amyloid type was available in 18 of these 42 cases and was AL in 15 cases, AA in 2 cases and AH in 1 case. Interestingly, AL amyloidosis was kappa type in 60% of our cases and in 67% of the previously reported cases reviewed by Rocken et al 4 This is in contrast to AL amyloidosis in general, in which twothirds of cases are of lambda type. 17 Forty-seven percent of patients with breast amyloidosis seen at our medical center had systemic AL amyloidosis.…”
Section: Discussioncontrasting
confidence: 63%
“…In our study, 3 of the 10 patients with associated hematologic disorder died of lymphoma/leukemia complications. Two of the three cases of breast amyloidosis reported by Rocken et al 4 and one of the seven cases reported by Charlot et al 3 were associated with invasive carcinoma (ductal in two patients and lobular in one patient). In contrast, only 1 of the 40 patients in our study had ductal carcinoma in situ and none had invasive cancer.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…13 Ten of these cases were of the AL systemic type and were not associated with an underlying condition. 13 In systemic amyloidosis, involvement of the eyelids can occur, but orbital involvement is uncommon.…”
Section: Discussionmentioning
confidence: 99%